Factors affecting the Behavior Intention to Make Purchases Online On E-Commerce - Shania Angelina; Dudi Anandya; Indarini Indarini (Program MM Universitas Surabaya, 2022)
This study aims to determine and analyze the factors that influence behavioral intentions to make purchases online with the object of research e-commerce. The focus of this research are performance expectancy, effort expectancy, social influence, anxiety, personal innovativeness, and behavioral intention to purchase online. Sources of data obtained by distributing online questionnaires. Data were collected through questionnaires distributed to 398 respondents an then analyzed using path analysis and MGA (Multigroup Analysis) with SPSS (Statistical Package for Social Sciences) and SmartPLS 3.0 software. The results showed that performance expectancy, effort expectancy, social influence, and personal innovativeness had a positive and significant influence on behavioral intention to purchase online for the entire group, but there was no difference in the effect between the two gender groups. On the other hand, anxiety has a negative and significant influence on behavioral intention to purchase online in both gender groups and has a significant difference in influence which is dominated by the female group compared to the male group.